Integrated management of pine wilt disease in Troia - Naves,Pedro (2018)
Troia is a sandy peninsula covered mainly by maritime pine, Pinus pinaster, forest which has suffered since 1999 the impact of pine wilt disease caused by the pinewood nematode Bursaphelenchus xylophilus. The nematode is dispersed by the insect vector Monochamus galloprovincialis. Over the years, intensive management of the forests involved annual sanitary felling of dead and wilted pines, the placement of baited traps to capture flying insects, and the preventive inoculation of pines with a nematicide/insecticide by micro-injection. These measures have been effective in the control of pine wilt disease and in the decrease of the insect pest populations.